Novel DER and OLTC management during islanded operation of MV microgrid - Laaksonen, Hannu; Hatziargyriou, Nikos (Institution of engineering and technology, 2025)
Importance of electricity distribution networks’ resiliency and supply reliability has been constantly increasing and due to that also interest towards momentary island operation and microgrids has grown. This paper proposes novel distributed energy resources’ (DERs’) and on-load tap-changers’ (OLTCs’) management concept in order to enable longer duration island operation of MV microgrid. Main focus of the studies is on medium-voltage (MV) network-connected battery energy storage system’s (BESS’s) voltage level control as well as on its interconnection transformer’s OLTC management during the isla nd operation. The PSCAD simulation studies show how the proposed MV BESS’s interconnection transformer OLTC control logic during MV microgrid’s island operation together with chosen minimum voltage control set value reduces the needed amount of current from the MV BESS and therefore the duration of the island operation can be increased. Based on the simulations, for example, with MV BESS voltage control set value 1.0 pu, the utilization of MV BESS OLTC can reduce 11 % the needed current from the MV BESS and when lowering voltage control set value to 0.96 pu, the BESS current can be even further reduced by 8 %. In addition, paper presents simulation results to indicate how MV microgrid reconnection can be successfully done also with the proposed novel MV BESS and OLTC control concept when having universal frequency-locked-loops (U-FLLs) on the inverter-based DERs. Based on the studies stable reconnection was possible even with ±145-160° angle difference.
Keywords: fi=Sähkötekniikka|en=Electrical Engineering|; fi=Sähkötekniikka|en=Electrical Engineering|